WatchAlert: Uma evolução do aplicativo fAlert para detecção de quedas em smartwatches - Almeida , Rodrigo L. A; Macedo, Alysson A.; Araújo, Ítalo Linhares de; Aguilar, Paulo Armando; Andrade, Rossana M. C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2016)
One of the biggest problems faced by the elderly population is the occurrence of falls. To help in the detection of such situations, sensors can be used. Based on this, firstly, it was created fAlert, an app that runs in a smartphone and uses accelerometer and microphone to detect falls. However, for a more precise drop detection, the smartphone would be located in the user’s chest. Due to the limitations of this, we not only evolve it to run in a smartwatch but also improve the way of fall detection. This evolution, called WatchAlert, uses the same sensors, accelerometer and microphone, and adds the gyroscope. Thus, WatchAlert performs the detection of falls with a less invasive and more natural way.